Chasing the elusive viscacha in Precolumbian textiles at the intersection of art and science. (April 2022) - Solazzo, Caroline; Phipps, Elena
Abstract: Precolumbian textiles from Peru played a central role in the development of Andean culture, and are primarily known to have been woven with a variety of native camelid hairs and cotton yarns. But close examination of some Andean textiles has revealed the presence of certain fibers, brown-grey or yellowish in their natural, undyed color, that are extremely fine and have special physical characteristics when observed under the microscope including pointed and elongated scale features, and a segmented medulla. The unusual fibers were postulated to come from the viscacha, a rodent from the Chinchillidae family that lives in the Western part of South America from Ecuador to Argentina. Indeed, the animal has been mentioned in sixteenth century historical chronicles and can be seen represented on Precolumbian and colonial-era tapestries. To identify these unusual fibers and trace their early use in Peruvian textile traditions, proteomics was used to characterize the hair proteome of viscacha and identify species markers in several selected textiles from museum collections. Reference samples of hairs were taken from known specimens for the most common species of viscacha ( Lagidium sp. and Lagostomus sp.) and specific peptide markers of keratins were identified by denovo sequencing and by comparison with keratin sequences from Chinchilla lanigera, the closest relative for which the genome has been sequenced. Thirteen Chinchilla- only markers, six Lagidium -only markers and seven Lagostomus -only markers were identified. Subsequently, yarns were analyzed from seven different textiles selected on the basis of visual assessment of their physical characteristics. Of these seven textiles, five were indeed matched to a Chinchillidae species using public sequences and further confirmed as mountain viscacha from the Lagidium genus by using the specific markers determined in this study. Highlights: Unusual fibers were found in certain Precolumbian Peruvian textiles through visual assessment. Fibers were hypothesized to be from viscacha, a rodent from the Chinchillidae family. The hair proteome of viscacha was characterized for plains and mountain viscachas. Keratin species markers were described for chinchilla, plain and mountain viscachas. Mountain viscacha fibers were identified in five out of seven textiles analyzed.